Spectroscopic Studies of the Interaction between Methyl Orange and Gemini Surfactant - Jia, F.; Gong, L.F.; Ni, R.J.; Su, G.M.; Yao, C. (Asian Journal of Chemistry, 2010)
The influence of two kinds of cationic surfactants on spectral properties of methyl orange in aqueous solutions has been investigated by means of UV-vis spectroscopy in various pH values and concentration range. For the Gemini14-methyl orange (MO) solutions, a hyperchromic shift was observed from 509-403 nm with the decrease of spectra absorption by increasing the pH values. Spectral behaviour of dye-surfactant solutions with varying concentrations of surfactants confirmed that electrostatic hydrophobic interactions between dye and surfactant played an important role. An H-type aggregation appeared in the concentration ratio 1:2 for Gemini14 and methyl orange, but in the CTAB solutions, the ratio was 1:1. The initial decrease of the absorbance resulted from dye-surfactant complex formation. It can be concluded that the amount of the cationic groups plays an important role in the complex formation.